Thank You My Heroes - Operation of sending back UMP and east zone IPTs students goes smoothly - Mohd Ferdaus, Musa (2020)
Kuantan, 14 May 2020 - The process of sending students back to their hometowns in Labuan, Sabah and Kuching, Sarawak was continued involving 18 students from Universiti Malaysia Pahang (UMP) and other higher education institutions (IPTs) in Pahang.